## Another variant of induction

Sometimes, the previous version is called weak induction compared to the following version where the you have a stronger assumption available for use in the induction step.

**Theorem** (Strong induction). Let $P$ be a predicate on $n \in \mathbb{N}$. Assume we have some $n_0 \in \mathbb{N}$ with

- a proof of $P(n_0)$ and
- a proof, for all $n \geq n_0$, that \((\forall~ n_0 \leq k \leq n, P(k)) \to P(n+1)\)

Then, we have a proof of $\forall~ n \geq n_0, P(n)$.

## **Proof**. (Expand to view)

We make a new predicate $$ Q(n) = \forall~ n_0 \leq k \leq n, P(n) $$ So a proof of $Q(n)$ is the same as proofs of each $P(k)$ for all $k$ between $n_0$ and $n$. Note that, for any $n \geq n_0$, we have $Q(n) \to P(n)$.

We use the usual version of induction to prove $Q(n)$ for all $n$. For the base case, we note that $Q(n_0) = P(n_0)$ which we have assumed we can prove.

For the induction step, we have assumed that we can prove $$ Q(n) \to P(n+1) $$ But $$ Q(n+1) = Q(n) \land P(n+1) $$ so we can prove $Q(n) \to Q(n+1)$. Appealing to (weak) induction, we can prove $Q(n)$ for all $n \geq n_0$. Since $Q(n)$ implies $P(n)$, we prove $P(n)$ for all $n \geq n_0$. ■

A Lean-version of the proof is below.

Why do we have this version? In general, $P(n) \to P(n+1)$ might be false where $(\forall k \leq n, P(k)) \to P(n+1)$ is true. We cannot use (weak) induction in this case but we can use strong induction.

**Example**. The Tribonacci sequence is a sequence defined recursively by \(a_0 = 0, a_1 = 0, a_2 = 1, a_n = a_{n-1} + a_{n-2} + a_{n-3} \text{ if } n \geq 3\) Let’s show that $a_n \leq 2^{n-3}$ for all $n \geq 3$ using strong induction.

Our base case is $n=3$. Then $a_3 = 1$ and $2^{3-3} = 1$.

Now assume that we know that $a_k \leq 2^{k-3}$ for $3 \leq k \leq n$. We have \(a_{n+1} = a_n + a_{n-1} + a_{n-2} \leq 2^{n-3} + 2^{n-4} + 2^{n-5}\) as long as $n \geq 5$. We will need to cover the cases of $n=3,4$ separately. We will circle back to this but for right now assume that $n \geq 5$. Then, we can use the inequality above. We have \(2^{n-3} + 2^{n-4} + 2^{n-5} = 2^{n-5}(4 + 2 + 1) = 7 \cdot 2^{n-5} < 2^3 \cdot 2^{n-5} = 2^{n-2}.\) Thus $a_{n+1} \leq 2^{n-2}$ as long as $n \geq 5$.

Assume that $n = 4$. Then we prove directly that $a_4 \leq 2$. We have $a_4 = a_3 + a_2 = 1 + 1 = 2 = 2^1$.

Assume that $n = 5$. Then $a_5 = a_4 + a_3 + a_2 = 2 + 1 + 1 = 4 = 2^2$.

These cover the missing cases above in the induction step. We can now appeal strong induction to get our conclusion.

In examples like the previous one, it makes sense to introduce another variant of induction: strong induction with multiple base cases. Here we cover some extra base cases before the induction step takes over.

**Corollary**. Let $P$ be a predicate on $n \in \mathbb{N}$. Assume we have $n_0, n_1 \in \mathbb{N}$ with $n_0 \leq n_1$ with

- proofs of each $P(n_0),\ldots,P(n_1)$ and
- a proof that, for each $n \geq n_1$, \((\forall~ n_0 \leq k \leq n, P(k)) \to P(n+1)\)

Then we have a proof of $\forall~ n \geq n_0, P(n)$.

Let’s do one more example of induction and recursion combined.

**Definition**. For $n, k \in \mathbb{N}$, the *binomial coefficient* $ \binom{n}{k}$ is defined recursively by \(\binom{n}{0}= 1, \binom{0}{k+1} = 0, \binom{n+1}{k+1} = \binom{n}{k} + \binom{n}{k+1}\)

**Lemma**. If $k > n$, then $\binom{n}{k} = 0$.

## **Proof**. (Expand to view)

We prove this via induction on $n$. The base case is $n = 0$. Since $k > 0$, we know that $k = k^\prime + 1$ for some $k^\prime \in \mathbb{N}$. Then by definition $\binom{0}{k^\prime + 1} = 0$.

Assume we know that $\binom{n}{k} = 0$ whenever $k > n$. Assume that $k > n+1$. We can again rewrite $k^\prime + 1 = k$. Then $$ \binom{n+1}{k^\prime+1} = \binom{n}{k^{\prime}} + \binom{n}{k^\prime +1} $$ Since $k^\prime > n^\prime$ and $k^\prime + 1 > n$, both these terms are $0$ by definition. ■

As an example, we compute \(\binom{5}{2} = \binom{4}{1} + \binom{4}{2} = \binom{3}{0} + 2\binom{3}{1} + \binom{3}{2} = 3 \binom{3}{0} + 3\binom{2}{1} + \binom{2}{2} \\ = 3 \binom{3}{0} + 3 \binom{2}{0} + 4 \binom{1}{1} + \binom{1}{2} = 3 \binom{3}{0} + 3 \binom{2}{0} + 4 \binom{1}{0} + 4 \binom{0}{1} = 10\)

Where do these numbers come from and why the name?

**Theorem** (Binomial formula). For any indeterminants $x$ and $y$ and any $n \in \mathbb{N}$ we have \((x+y)^n = \sum_{k=0}^n \binom{n}{k}x^{n-k}y^k\)

## **Proof**. (Expand to view)

We prove this using induction $n$. For the base case of $n=0$, we have $(x+y)^0 = 1$ and $$ \sum_{k=0}^0 \binom{n}{k} x^{-k} y^k = \binom{0}{0} = 1 $$ Assume that $$ (x+y)^n = \sum_{k=0}^n \binom{n}{k} x^{n-k} y^k $$ Then $$ (x+y)^{n+1} = (x+y)(x+y)^n = (x+y) \sum_{k=0}^n \binom{n}{k} x^{n-k}y^k = \\ x \sum_{k=0}^n \binom{n}{k} x^{n-k}y^k + y \sum_{k=0}^n \binom{n}{k} x^{n-k}y^k = \\ \sum_{k=0}^n \binom{n}{k} x^{n+1-k}y^k + \sum_{k=0}^n \binom{n}{k} x^{n-k}y^{k+1} $$ Now we combine terms into a single sum. For $0 \leq j \leq n+1$, we get two contributions: $\binom{n}{j} x^{n+1-j}y^j$ from the first and $\binom{n}{j-1} x^{n+1-j} y^j$ from the second. Thus $$ (x+y)^{n+1} = \sum_{j=0}^{n+1} \left( \binom{n}{j} + \binom{n}{j-1} \right) x^{n+1-j}y^j \\ = \sum_{j=0}^{n+1} \binom{n+1}{j} x^{n+1-j}y^j $$ Appealing to induction, we get our desired conclusion. ■

**Example**. The Binomial Theorem allows access to many interseting formula about binomial coefficients. For example, if we take $x=y=1$, we get \(2^n = \sum_{k=0}^n \binom{n}{k}\) If we take $x = 1, y = -1$, then we get \(0 = \sum_{k=0}^n (-1)^k \binom{n}{k}\)